Management of Abdominal Management of abdominal Typhoid in a 22 years old women without regular diet and lack of PHBS knowladge. especially washing hands before eating: Typoid fever, PHBS and Diet - Tri Agustina Dewi; Rika Lisiswanti (Medula, 2026)
Typhoid fever is a potentially fatal multisystem infectious disease that remains a significant public health problem in Indonesia, particularly in areas with poor sanitation and inadequate implementation of clean and healthy living behavior (PHBS). We report a case of a 22-year-old woman who presented with continuous fever for approximately three days prior to admission, worsening in the afternoon and evening, accompanied by chills, headache, dizziness, nausea, vomiting, epigastric pain, and constipation. The patient had a history of irregular dietary habits, frequent consumption of street food, and poor hand hygiene practices, especially failure to wash hands before meals. Physical examination revealed a coated tongue and epigastric tenderness, while laboratory findings showed a Widal O titer of 1/320 supporting the diagnosis of abdominal typhoid fever. The patient was managed with chloramphenicol, antipyretics, intravenous fluids, bed rest, and a low-fiber diet, along with comprehensive education regarding PHBS implementation, particularly proper handwashing and regular dietary patterns. This case highlights that irregular eating habits and inadequate knowledge and practice of PHBS play an important role in the occurrence of abdominal typhoid fever, emphasizing the need for comprehensive management combining medical therapy and health behavior education to prevent recurrence and disease transmission.